2019
DOI: 10.3389/fpsyt.2019.00623
|View full text |Cite
|
Sign up to set email alerts
|

Significant PTSD and Other Mental Health Effects Present 18 Months After the Fort Mcmurray Wildfire: Findings From 3,070 Grades 7–12 Students

Abstract: Background: The May 2016 wildfire in Fort McMurray, Alberta, Canada forced evacuation of the population of 88,000 individuals and destroyed 10% of the homes. Youth are particularly impacted by disaster. Methods: Eighteen months after the wildfire, Fort McMurray Public and Catholic Schools surveyed 3,252 of the 4,407 students in Grades 7–12 to determine possible long-term psychological impacts. The survey included validated measurement scales for post-traumatic stress disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 42 publications
(71 reference statements)
2
60
0
1
Order By: Relevance
“…A number of studies suggest mental health effects of wildfire disasters on children. Surveys of the middle and high school students in a small Canadian city, 18 months after a large wildfire caused evacuation of the entire city, showed elevated rates of depressive symptoms among youth in that city compared to youth in a control city [61,62]. It is worth noting, however, that these effects cannot be clearly attributed to wildfire smoke as the trauma associated with widespread evacuation likely contributes to mental health.…”
Section: Health Effects Of Other Aspects Of Wildfire Disastersmentioning
confidence: 97%
“…A number of studies suggest mental health effects of wildfire disasters on children. Surveys of the middle and high school students in a small Canadian city, 18 months after a large wildfire caused evacuation of the entire city, showed elevated rates of depressive symptoms among youth in that city compared to youth in a control city [61,62]. It is worth noting, however, that these effects cannot be clearly attributed to wildfire smoke as the trauma associated with widespread evacuation likely contributes to mental health.…”
Section: Health Effects Of Other Aspects Of Wildfire Disastersmentioning
confidence: 97%
“…According to the research of the Population Reference Bureau, during the 2004 Indian Ocean tsunami, women and children were more likely to suffer physical and psychological problems than men were (47). Moreover, many studies indicate that children, especially those under 8 years of age, are especially vulnerable to psychological and mental health problems following disasters (48)(49)(50)(51)(52)(53). The most common symptoms and diagnoses consist of anxiety disorders, such as PTSD, panic, and phobias.…”
Section: Agementioning
confidence: 99%
“…This aligns with the World Health Organization’s guidelines for providing psychological first aid to survivors of trauma, including bushfires 26 . The need for preventive and promotive long term mental health support for those impacted by bushfire was also highlighted 17,23 . In addition, it was suggested that the support for children should focus on assisting them to strengthen and maintain social relationships, as emotional support appeared to play a protective and promotive role, and encouraged higher levels of prosocial behaviour 27 .…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any research on effectiveness of interventions aimed at reducing the risk of the impact of bushfires. Gibbs et al observed, “there is a critical shortage of evidence for post‐disaster intervention effectiveness for all ages, due to the ethical and pragmatic challenges of conducting research in post‐traumatic settings.” 21 Although several studies suggested screening children and adolescents after bushfires to identify those who may be at risk of mental health sequelae 17,22 and providing long term mental health support, 17,23 guidance on delivering the required support was lacking.…”
Section: Discussionmentioning
confidence: 99%